Republic of Madagascar : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper analyses tax revenue mobilization potential in Madagascar and lessons learned from successful episodes in sub-Saharan African (SSA) countries. The analysis shows that there is a significant tax potential including through a possible broadening of the tax base, notably for consumption taxation; and underscores the importance of a comprehensive revenue strategy, including by combining reforms in tax policy and in tax and customs administrations. Significant progress has been made in terms of organization, simplification of procedures, management, and dialogue with the taxpayers. Communication between the two tax administrations could be improved. The tax administrations should notify each other if a case of fraud. Also, the domestic tax administration should have access to customs import/export data: many importers are active and make customs declarations without being identified by the domestic tax administration. Given the weaknesses in the provision of public services, social dialogue and consultation are important to explain the rationality of the tax system and the use of the tax revenue by the State.